Pembagian Peti Kemas Kosong di PT. X - Brigitte Trista Indah Yudhiana Sutrisno; I Gede Agus Widyadana (Jurnal Titra, 2017)
PT. X is a company engaged in the field of shipping by providing services in the form of container rental and send the container to the ship owned by the company. The loading and unloading of containers from aboard requires a document called Unloading Order, containing the status, quantity, and destination of the depot from the unloaded container. The distribution of empty containers is currently only done based on estimates so that there is repositioning from one depot to another because it does not have the required containers. The purpose of the research is to find the minimum inventory value that can be used as a reference to the distribution of empty containers to the depots so as to reduce the repositioning. The repositioning cost incurred by the company in 2016 is Rp 284.000.000,00 only for fuel expenditure. The minimum inventory values search using simulation methods in Excel. The simulation is an improvement model of the current condition. The model of improvement performed is the empty container distribution is done based on the difference between the current inventory amount and the minimum inventory value which is the decision variable.In addition, repositioning is also done if the depot has inventory amount below minimum inventory value or above depot capacity. Improved models can eliminate repositioning due to lack of containers. The minimum inventory value obtained from the simulation for Depot 4 has an average of 107 units, Depot 8 is 50 units, and Depot Japfa is 266 units. The average value is a combination of the three empty container grades, A, B, and C. The minimum inventory values obtained from the simulation are then put into Unloading Order to facilitate the distribution of empty containers.